"Smurf, Smurf, Gammelsmurf - du är skyldig mig en läsk!" - Skott, Fredrik (Tidsskrift for kulturforskning, 2016)
The ritual "saying the same word at the same time" is known in large parts of the world. This article is focusing on how the ritual has been performed in Sweden, from the 1800s to the present. By following the ritual over time continuity, variation, change and not the least the interaction between them are discussed; how tenacious structures as well as rapid changes have contributed to the fact that the ritual not only has survived through two centuries, but also have spread over large geographical areas. In the article I examine whet-her, and if so how, the change of the ritual reflects changing norms and values over time.